Broadband photodetector based on SnTe nanofilm/n-Ge heterostructure. (15th October 2022) - Song, Liyuan; Tang, Libin; Hao, Qun; Teng, Kar Seng; Lv, Hao; Wang, Jingyu; Feng, Jiangmin; Zhou, Yan; He, Wenjin; Wang, Wei
Abstract: Combining novel two-dimensional materials with traditional semiconductors to form heterostructures for photoelectric detection have attracted great attention due to their excellent photoelectric properties. In this study, we reported the formation of a heterostructure comprising of tin telluride (SnTe) and germanium (Ge) by a simple and efficient one-step magnetron sputtering technique. A photodetector was fabricated by sputtering a nanofilm of SnTe on to a pre-masked n-Ge substrate. J – V measurements obtained from the SnTe/n-Ge photodetector demonstrated diode and photovoltaic characteristics in the visible to near-infrared (NIR) band (i.e. 400–2050 nm). Under NIR illumination at 850 nm with an optical power density of 13.81 mW cm −2, the SnTe/n-Ge photodetector exhibited a small open-circuit voltage of 0.05 V. It also attained a high responsivity ( R ) and detectivity ( D *) of 617.34 mA W −1 (at bias voltage of −0.5 V) and 2.33 × 10 11 cmHz 1/2 W −1 (at zero bias), respectively. Therefore, SnTe nanofilm/n-Ge heterostructure is highly suitable for used as low-power broadband photodetector due to its excellent performances and simple device configuration.